Sneakers [videorecording (Blu-Ray + DVD)] - Horner, James (Universal Studios Home Entertainment, 2015)
Computer expert Martin Bishop heads a team of renegade hackers who are routinely hired to test security systems. When government agents blackmail the ;sneakers' into carrying out a covert mission of tracking down a top-secret black box, Bishop's team find themselves embroiled in a dangerous operation. They make a stunning discovery; the device has the capability to decode all existing encryption systems around the world.